Intrusive memories and rumination in patients with post-traumatic stress disorder: a phenomenological comparison. - Speckens, A; Ehlers, A; Hackmann, A; Ruths, F; Clark, D (2007)
The aim of the study was to investigate the phenomenological differences between intrusive memories and rumination in PTSD. The study population consisted of 31 patients with PTSD referred for cognitive behavioural therapy to specialist services. A semi-structured interview was used to examine the characteristics of the most prominent intrusive memory and rumination. Intrusive memories were predominantly sensory experiences of short duration, whereas rumination was predominantly a thought process of longer duration. Shame was associated more with rumination than with intrusive memories. Anxiety, helplessness, numbness, and threat were greater at the time of the trauma than when experiencing the intrusive memory. In contrast, feelings like anger and sadness were greater when experiencing intrusive memories than at the time of the event. The distinction between intrusive memories and rumination is of clinical importance as intrusive memories usually decrease with imaginal reliving of the trauma, whereas rumination may require different therapeutic strategies, such as rumination-focused or mindfulness-based cognitive therapy.